2014
DOI: 10.1007/978-3-319-12304-2_14
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors in Production Systems

Abstract: Information and communication technology (ICT) is getting smaller and faster at a dashing pace and is increasingly pervading production technology. This penetration of ICT within and across production technology enables companies to aggregate and utilize massive amounts of data of production processes, both horizontally (across different products) and vertically (from machine level, over the shop floor, to the supply chain level). Presumably, this yields in Smart Factories with adaptable manufacturing processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…From this it can be concluded that task performance profits from operators' high perceptual speed. However, from an occupational ergonomic point of view it is much more important to argue from the other side: Not all persons can rely on outstanding cognitive competencies, especially as future work generations are characterized by highly diverse skills [7] with very different educational and professional backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From this it can be concluded that task performance profits from operators' high perceptual speed. However, from an occupational ergonomic point of view it is much more important to argue from the other side: Not all persons can rely on outstanding cognitive competencies, especially as future work generations are characterized by highly diverse skills [7] with very different educational and professional backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Users reported that the increasing amount of available data delivered by ERP systems in combination with suboptimal information representation leads to high (perceived) workload and a low motivation to use these systems [3]. As strategic decisions still depend on humans in the loop who have to perceive, understand and process increasingly complex information and to make quick and correct decisions with considerable consequences for the effectiveness of the production process [2,7], the usability and the adequacy of the information visualization are critical factors [2,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…a value stream, so it will lead to IT-enable mass customization (Brauner & Ziefle, 2015). Internet of things and digitalized smart machines synchronize themselves right from the start to the end of production processes within the value chain.…”
Section: Smart System Enables Identity and Communication Between Eachmentioning
confidence: 99%
“…Cyber physical system can check the availability of particular employee for the specific operations thus reducing the mangers effort in maintaining workforce. In this way assessment of workforce in term of their availability, speed precision and performance could be simplified by worker support system (Brauner & Ziefle, 2015).…”
mentioning
confidence: 99%
“…Individual people and their interactions are considered as a critical success factor in the development of new systems, including production processes (Yauch 2007;Alves et al 2012;Brauner and Ziefle 2015). It is the ability of individuals to reflect-in-action (Schön and Wiggins 1992), often through informal communication and self-organized teamwork that can lead to the discovery of new requirements and conceptual solutions, thus leading the design process in new directions (Gero and Kannengiesser 2014).…”
Section: Individuals and Interactions: Support Through Notational Simmentioning
confidence: 99%